Faktor Yang Mempengaruhi Loyalitas Nasabah Pada BTN Syariah KC Solo Dengan Kepuasan Sebagai Variabel Intervening - Fahrur Rozi; Ahmad Samingan (Al-bank: Journal of Islamic Banking and Finance, 2024)
The study aims to analyze the factors that influence customer loyalty with satisfaction as a mediating variable. This research method uses quantitative methods with a sample size of 100 respondents. The data used in this research is primary data obtained from filling out questionnaires by respondents. The results of this study indicate that communication has no effect on customer loyalty, complain handling has no effect on customer loyalty, service quality has no effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, communication has a positive and significant effect on customer satisfaction, complain handling has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, satisfaction can mediate communication to customer loyalty, satisfaction can mediate complain handling to customer loyalty, satisfaction can mediate service quality to customer loyalty, satisfaction can mediate service quality to customer loyalty